Comparison of Transient Stability Response for MMPS using UPFC with PI and Fuzzy Logic Controller - Rashid H. AL-Rubayi; Luay G. Ibrahim (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
The increasing pressure on the power system increases the complexity that is becoming a concern for the stability of the power system and mainly for transitory stability. To operate the system in the event of faults, Flexible AC Transmission System (FACTS) devices are used that provide opportunities to control power and vibrations damping. This paper deals with the two control strategies of the Unified Power Flow Controller (UPFC) to damping the system oscillations stability. The stability of the Multi-Machine Power System (MMPS) was analysed with the presence of UPFC. The first strategy is the traditional PI controller (PI-C) with UPFC, and the second strategy is the proposed Fuzzy Logic controller (FL-C) proposed for UPFC device along with PI controller. The MATLAB R2014a was used in all simulations. Based on the results,  FL-C   for  UPFC device along with the PI controller has proven its superiority by has enhanced response to the system, thus minimized in the transitions overshoot and undershoot, and has lower ripple compared to traditional PI-C, both with and without UPFC.